Vilnius in Jurgis Kunčinas’s Tūla: From Urban Practices towards Textual Strategies - Bidlauskienė , Gintarė (Colloquia, 2019)
A thorough review of studies carried out on the urban aspect of Jurgis Kunčinas’s novel Tūla has revealed a tendency to ignore the temporal aspect. Thus, the article complements existing research with the analysis in geocriticism, urban studies, and intermediality (intertextuality). It focuses on the representation of Vilnius created in Tūla, aiming to reveal the relationship between the textual form of the novel and the image of the city it depicts. The analysis examines the structure of Kunčinas’s city representation, its cartographic accuracy and dominant motifs: the sensory experiences of the city related to the gaze and walking of the main character. These two practices create the spatial logic of the novel: different gazing modes make the urban space visible, and the main character’s walking links objects in space. The junctions that he forms along his paths are also part of the novel’s structure. This way, the depicted city objects become landmarks of the narrative. Finally, the analysis of the representation of Vilnius in Tūla highlights the links between the construction of the fictional urban space and the structure of the city novel. In the novel, different techniques used to capture Vilnius, as well as different ways of experiencing the city are related to text’s content and its narrative form. On the other hand, the analysis enables to consider the intermedial aspects of the image of Vilnius created by Kunčinas, and especially their relation to visual intertexts that have not yet been examined by other researchers
Keywords: : literary representation of Vilnius; Jurgis Kunčinas; geocriticism; literary urban studies